Case report: Cryptogenic giant brain abscess caused by Providencia rettgeri mimicking stroke and tumor in a patient with impaired immunity - Zhao, Yu; Lian, Baorong; Liu, Xudong; Wang, Qizheng; Zhang, Daxue; Sheng, Qi; Cao, Liming (Frontiers in Neurology, 2022)
Cryptogenic brain abscess with high lethality can be easily misdiagnosed. However, cryptogenic brain abscess caused by Providencia rettgeri is rarely reported. We present a case of a cryptogenic Providencia rettgeri brain abscess and analyzed the clinical manifestations, imaging findings, treatment, and outcome to improve the level of awareness, aid in accurate diagnosis, and highlight effective clinical management. A 39-year-old man was admitted to the hospital after experiencing acute speech and consciousness disorder for one day. The patient had a medical history of nephrotic syndrome and membranous nephropathy and used immunosuppressants. Magnetic resonance imaging revealed huge, space-occupying lesions involving the brain stem, basal ganglia, and lobes without typical ring enhancement that mimicked a tumor. Initial antibiotic treatment was ineffective. Subsequently, pathogen detection of cerebrospinal fluid using metagenomic next-generation sequencing revealed Providencia rettgeri. The patient was intravenously administered maximum ampicillin for 5 weeks, and symptoms resolved. Cryptogenic Providencia rettgeri brain abscess is prone to occur in patients with impaired immunity. Our patient exhibited a sudden onset with nontypical neuroimaging, which required differentiation from stroke and brain tumor. Metagenomic next-generation sequencing was important in identifying the pathogen. Rapid diagnosis and appropriate use of antibiotics were key to obtaining a favorable prognosis.